Factors Affecting Covid-19 Vaccine Acceptance Among Residents Of Adenta, Abokobi And Frafraha - Adade, W.A. (University Of Ghana, 2022)
Background: Vaccination is an important part of public health, and an important way of preventing the spread of contagious, dangerous, and deadly diseases thus saving lives. The introduction of COVID-19 vaccines has been a game changer in reducing hospitalization, death, and risk of severe complications from COVID-19. Success of vaccination programs is not only dependent on efficacy and safety of vaccines, but critically dependent on public perception and acceptability of the vaccines. Therefore, vaccine acceptance among the public and healthcare workers appears to be critical determinant on successful deployment and control of pandemics. Therefore, it is important to understand the factors that determine acceptability of the COVID-19 vaccine among the public. Objective: The objective of this study was to determine factors associated with COVID-19 vaccine acceptance among residents in the Adenta, Frafraha and Abokobi communities. Methods: A quantitative cross-sectional study using structured questionnaire was conducted to collect data on factors or determinants of COVID- 19 vaccine acceptance among residents of Adenta, Frafraha and Abokobi. Result: Most of the study participants agreed that there is currently no effective treatment for COVID-19 disease (n=252 (58.3%)) and are awaremany people are taking the COVID-19 vaccine (n=263 (60.9%)). Generally, 19.4% of community members had high knowledge on COVID-19 vaccine. An estimated 38.7% and 41.9% had moderate / low Knowledge and awareness on COVID-19 disease and COVID-19 vaccine respectively. Acceptance of COVID-19 vaccine was high (63.4%) in the Adenta community as compared to Frafraha (29%) and Abokobi (6.5%). There was a significant association between marital status and acceptance of COVID-19 vaccine (2=12.140: p=0.002). There was also a significant association between religion (2=6.971: p=0.031), ethnicity (2=10.533: p=0.005) and acceptance of COVID-19 vaccine. Conclusion: About 6 in 10 community members accepted the COVID-19 vaccine. Acceptance of COVID-19 vaccine was highest among residents of Adenta, an urban community compared to Frafraha and Abokobi. There is inadequate knowledge on COVID-19 vaccine in the communities studied. Recommendation: Public education should be conducted by the relevant stake holders in the three communities to improve vaccine information awareness and knowledge. Health practitioners, media personnel, government officials, community representatives, political groups, and the local assembly must all take the COVID-19 vaccine publicly. Communities aware of the acceptance of the vaccine by role models were more likely to accept the vaccine as compared to those who were unaware of acceptance.
MPH
Keywords: Covid-19; Vaccine; Adenta; Abokobi; Frafraha